Serum Biochemical Alterations in Dogs Affected by Hepatic Dysfunction in Jaipur, Rajasthan, India - , Nabeel Khan Pathan; , Nazeer Mohammed; , Rashmi Singh; , Pradeep Kumar; , Dharm Singh Meena; , Harshita Rathore (Archives of Current Research International, 2025)
Hepatic dysfunction in dogs manifests through a variety of clinical and subclinical signs, many of which are reflected in changes in serum biochemical parameters. The liver plays a pivotal role in metabolism, detoxification, protein synthesis, and regulation of various biochemical processes. Alterations in serum markers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), bilirubin, bile acids, urea, cholesterol, and serum proteins serve as essential indicators for diagnosing and monitoring liver diseases. The present study was aimed to assess biochemical changes in dogs with hepatic dysfunction. During the period from August 2024 to January 2025, a total of 200 dogs with suspected hepatic dysfunction on the basis of clinical signs were screened in this study from Jaipur, Rajasthan, India. Serum Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Alkaline Phosphatase (ALP), Gamma-Glutamyl Transferase (GGT), total bilirubin, blood glucose and total protein were measured on an automated biochemical analyzer. Among 200 suspected dogs, twelve (12) were diagnosed with hepatic dysfunction which was compared with ten (10) healthy control dogs. Relevant biochemical changes found in these dogs were increased activities of ALT, AST, ALP, GGT and total bilirubin, with reduction in the levels of total protein and glucose. These observations indicate that biochemical profiling is a useful method for diagnosing and monitoring hepatic dysfunction in dogs.